Penjaminan Mutu Pendidikan Islam Di STAI Darul Qur’an Aceh Tenggara - Khairudin, Khairudin (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
The development and management of Islamic educational institutions in achieving excellence is a matter that needs to be constantly updated and improved so that education continues to exist in responding to the challenges of the times and the needs of the wider community and the industrial world. Because education is believed to be the main foundation in building a nation's civilization, its quality must be maintained in order to produce superior, noble and competitive governance and graduates. This study aims to reveal the position and role of quality assurance of Islamic education in Islamic religious higher education institutions. This research is a descriptive qualitative type with data collection techniques through observation, interviews and document studies at the Darul Qur’an Aceh Tenggara. The results of this study indicate that the Quality Assurance of Islamic Education at the Darul Qur'an College has not fully run well and the elements in quality assurance such as education personnel, educational facilities and infrastructure, curriculum and evaluation have also not run fully in order to produce professional governance. , quality and quality of graduates who are absorbed in the community, humanistic services to produce outcomes in accordance with the mandate of the Act. This is because the Darul Qur'an College is still relatively new even though the Foundation has previously implemented pesantren education at the MTs and MAS levels.